# Law of cosines

(Difference between revisions)
 Revision as of 09:37, 30 May 2011 (edit) (→Distance Formula)← Previous diff Revision as of 10:41, 30 May 2011 (edit) (undo) (→example triangulation)Next diff → Line 33: Line 33: $c^{2} = (a^{2}+b^{2}-2ab \cos C+b^{2}$ $c^{2} = (a^{2}+b^{2}-2ab \cos C+b^{2}$ - ==example triangulation== + ==Example Triangulation== + Complete the triangle using the law of cosines. + + [[Image:SAS triangle.jpg]] + + To find the side length $c$,

## Revision as of 10:41, 30 May 2011

The law of cosines is a formula that helps in triangulation when two or three side lengths of a triangle are known. The formula relates all three side lengths of a triangle to the cosine of a particular angle.

$c^{2} = a^{2} + b^{2} - 2ab \cos C$

When to use it: SAS, SSS.

## Proof

Let $\vartriangle ABC$ be oriented so that $C$ is at the origin, and $B$ is at the point$(a,0)$.

### Distance Formula

$distance = \sqrt {(x_{2}-x_{1})^{2} + (y_{2}-y_{1})^{2}}$

$c$ is the distance from $A$ to $B$.

Substituting the appropriate points into the distance formula gives us

$c = \sqrt {(a-b \cos C)^{2} + (0-b \sin C)^{2}}$

Squaring the inner terms, we have

$c = \sqrt {(a^{2}-2ab \cos C+b^{2} \cos^{2} C) + (b^{2} \sin^{2} C)}$

Since $\cos^{2} C + \sin^{2} C = 1$,

$c = \sqrt {(a^{2}+b^{2}-2ab \cos C+b^{2}}$

Square both sides for

$c^{2} = (a^{2}+b^{2}-2ab \cos C+b^{2}$

## Example Triangulation

Complete the triangle using the law of cosines.

To find the side length $c$,